(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
Geographical position makes Bangladesh globally as one of the most vulnerable countries to climate change. It is observed that climate change has become a burning issue jeopardizing the agricultural production in the country. Considering the issue, adoption of climate smart agriculture (CSA) is indispensable for mitigating climate change by reducing emissions, capturing the atmospheric carbon and storing it in biomass and soil. The study reviewed the literature to evaluate the potentiality of agroforestry practices as climate smart agriculture to mitigate climate change impacts. Agroforestry has traditionally contributed to climate resilience in Bangladesh by integrating trees and/or crops into different land use practices. Agroforestry systems enhance resilience to climate change through increasing tree cover, carbon sequestration, increasing production, reducing threats to associated crops, creating favourable microclimate to support associated crops, reducing harvest pressure on natural forests, conserving biodiversity and cycling nutrients. Globally 23 countries recognize agroforestry as a mitigation priority, whereas 29 as an adaptation priority. Bangladesh has potential to expand agroforestry practices to mitigate climate change and boost food security. From socioeconomic and ecological point of views as well, agroforestry offers strong potential to evolve climate smart agricultural practices supporting food security, and adaptation and mitigation. Agroforestry practices should increase in climate vulnerable agroecosystems of Bangladesh. Int. J. Agril. Res. Innov. Tech. 11(1): 49-59, June 2021